2021
DOI: 10.1055/s-0041-1722821
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Hard-Tissue and Soft-Tissue Changes following Fixed Functional Appliance Treatment in a Skeletal Class II Malocclusion Using Forsus and PowerScope

Abstract: Introduction The purpose of this study was to evaluate and compare the skeletal, dentoalveolar and soft-tissue effects of 2 fixed functional appliance; Forsus Fatigue Resistance Device (FFRD) and PowerScope appliance in treating patients with skeletal class II division 1 malocclusion. Materials and Methods This comparative prospective two-group study included 20 patients with a mean age of 11.2 ± 1.6 years with skeletal class II malocclusion with retrognathic mandible. One group was treated with FFRD, and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
6
4
1
Order By: Relevance
“…Regarding the maxillomandibular relationship, there was a statistically significant (P ≤ 0.05) decrease of ANB angle that accounted for the minimal improvement of the sagittal intermaxillary jaw relationship. This was agreed with the results of studies (11,14,16,17,19,23,24,28) using PowerScope appliance and studies (20,21,22) using MARA, FFRD, and TFBC appliances. While a study (29) using Eureka Spring found no statistically significant change in the ANB angle.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 90%
See 4 more Smart Citations
“…Regarding the maxillomandibular relationship, there was a statistically significant (P ≤ 0.05) decrease of ANB angle that accounted for the minimal improvement of the sagittal intermaxillary jaw relationship. This was agreed with the results of studies (11,14,16,17,19,23,24,28) using PowerScope appliance and studies (20,21,22) using MARA, FFRD, and TFBC appliances. While a study (29) using Eureka Spring found no statistically significant change in the ANB angle.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 90%
“…There was a statistically significant (P ≤ 0.05) decrease in SNA angle which indicated the effect of Powerscope appliance on the restriction of the maxillary base that was agreed with the results reported by other Powerscope studies (23,24,16) in addition to studies (25,26,27) using Churro Jumper, Forsus Nitinol Flat Spring (FNFS), Jasper Jumper (JJ) and Sabbagh Universal Spring 2 (SUS 2) appliances. On the contrary, studies (11,14,18,19,17) using Powerscope appliance and other studies (20,21,22) using Mandibular Anterior Repositioning Appliance (MARA), Forsus Fatigue Resistant Device (FFRD) and Twin Force Bite Corrector (TFBC) appliances showed no statistically significant changes happened to SNA angle and consequently to the maxilla.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 89%
See 3 more Smart Citations